Assessment of Life-Cycle Carbon Footprint Reduction Potential through Green Roof and Vertical Farming Integration in Urban High-Rise Buildings - Rahman Abdillah; Wawan Hermawansyah; Ibnu Adkha (Green Engineering: International Journal of Engineering and Applied Science, 2024)
Rapid urbanization in major cities has led to the decreasing availability of green spaces, exacerbating urban challenges such as the Urban Heat Island (UHI) effect, high energy consumption in buildings, and air pollution. In response, green architecture innovations like green roofs and vertical farming present opportunities for reducing carbon footprints and improving urban sustainability. This study explores the potential for life-cycle carbon footprint reduction through the integration of green roofs and vertical farming systems in high-rise buildings, focusing on energy savings, environmental impact, and air quality improvements. Using Life-Cycle Assessment (LCA) methodology, the research evaluates carbon emissions reduction, operational energy savings, and ecosystem benefits from different building scenarios. Simulation models were developed for conventional high-rise buildings and those incorporating green roofs and vertical farming. EnergyPlus, SketchUp, and SimaPro software were used for energy consumption calculations and carbon emissions modeling. The study analyzes various intervention scenarios-baseline (no vegetation), green roof only, vertical farming only, and a combined system-based on tropical climate data from cities like Jakarta, Surabaya, and Kuala Lumpur. Results reveal that the integration of both green technologies significantly reduces cooling demand, lowers CO₂ emissions, and improves urban microclimates by reducing surface temperatures and enhancing air quality. Policy recommendations and guidelines for adopting green construction practices in tropical regions are provided, alongside suggestions for future research on optimizing these technologies, conducting economic modeling, and evaluating multi-building approaches at a district scale.